2012
DOI: 10.1007/s11748-012-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chest wall reconstruction with titanium plate sandwiched between two polypropylene sheets

Abstract: Extensive sternal resection carries the risk of difficult reconstruction and surgical complications. A 79-year-old woman underwent sternal resection and reconstruction for sternal chondrosarcoma. However, 18 months after the first operation, she developed six metastatic tumors on the anterior chest wall. She underwent subtotal sternectomy and rib resection, leaving a defect measuring 17 × 14 cm. Reconstruction of the anterior chest wall using a titanium plate sandwiched between two polypropylene mesh sheets is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…In 2013, Berthet et al conducted chest wall reconstruction with titanium alloy plates on 11 patients with primary or secondary chest wall infections, and none had recurrent infection 6 months after operation except 1 died, therefore the authors believed that osseous chest wall reconstruction with titanium alloy plates concomitant with tissue repair had reliable, safe and rapid clinical efficacy on patients with severe chest wall infections (Berthet et al, 2013). Matsumoto et al reported the application of chest wall reconstruction with titanium alloy plate on 1 case of chest wall chondrosarcoma with chest wall defect 17×14 cm in size after surgical resection and the result showed that no scoliosis was found during 12 months of follow-up after operation and the thorax movement range was satisfactory (Matsumoto et al, 2012).…”
Section: Value Of Porous Titanium Alloy Plates For Chest Wall Reconstmentioning
confidence: 99%
“…In 2013, Berthet et al conducted chest wall reconstruction with titanium alloy plates on 11 patients with primary or secondary chest wall infections, and none had recurrent infection 6 months after operation except 1 died, therefore the authors believed that osseous chest wall reconstruction with titanium alloy plates concomitant with tissue repair had reliable, safe and rapid clinical efficacy on patients with severe chest wall infections (Berthet et al, 2013). Matsumoto et al reported the application of chest wall reconstruction with titanium alloy plate on 1 case of chest wall chondrosarcoma with chest wall defect 17×14 cm in size after surgical resection and the result showed that no scoliosis was found during 12 months of follow-up after operation and the thorax movement range was satisfactory (Matsumoto et al, 2012).…”
Section: Value Of Porous Titanium Alloy Plates For Chest Wall Reconstmentioning
confidence: 99%
“…Radical operations in tumors, traumatic injuries, cardiosurgery intervention sequences lead to the necessity of replacing defects of the rib bar [1 ,2, 3]. А variety defects of available reconstructive techniques, first of all, testifies to the lack of а multipurpose effective method of the chest rib replacement [4,5,6,7]. The main demands for the implants are the following: biocompatibility, corrosion stability, ability to maintain the fixed form for а long time [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This tumour appears as a radiolucent mass originating from the medullary region of the bone and is usually associated with cortical destruction and stippled calcification. Surgery in the form of radical en bloc excision and immediate reconstruction is the key to the management of primary sarcomas of the sternum [2][3][4][5][6][7]. Surgery alone is potentially curative in a majority of the cases, with the 10-year survival rate approaching 97 %.…”
mentioning
confidence: 99%
“…Sternal resection can potentially result in large defects requiring complex reconstructions and various reconstruction techniques using prosthetic or homologous materials that have been described [2][3][4][5][6][7]. Skeletal reconstruction is considered not necessary for defects <5 cm in diameter.…”
mentioning
confidence: 99%
See 1 more Smart Citation